Mechanical vibration may be a novel adjuvant approach to promoting stability and retention following orthodontic treatment - Chunxiang Zhang; Linkun Zhang; Xiaomei Xu; Peipei Duan; Hongmei Wu (Wolters Kluwer Medknow Publications, 2014)
Introduction: Orthodontic tooth movement occurs as a consequence of paradental tissue remodeling in response to applied mechanical forces. Retention is a necessary procedure to prevent relapse when orthodontic appliances are removed. Developing new methods to promote stability and retention following orthodontic treatment has always been desired. Recent studies have demonstrated the favorable effects of low magnitude, high frequency (LMHF) mechanical vibration on bone homeostasis through an ability to stimulate cell metabolism and to enhance osteoblast proliferation, osteoblastic gene expression and bone formation. The Hypothesis: In this paper, we propose that LMHF mechanical vibration is a viable adjuvant method to accelerate bone and periodontal tissue remodeling, thereby promoting stability and shortening retention time. Evaluation of the Hypothesis: Much effort has been made to explore therapies to prevent relapse and shorten orthodontic retention time with limited success. LMHF mechanical vibration may be a promising approach to accelerate alveolar bone remodeling, ultimately promote stability and shorten retention time.